Inflammatory indexes and anemia in chronic kidney disease: correlation and survival analysis of the National Health and Nutrition Examination Survey 2005–2018 - Shaojie Fu; Jingda Huang; Zhenbang Feng; Haitao Wang; Hongzhao Xu; Meiyan Wu; Fuzhe Ma; Zhonggao Xu (Renal Failure)
Background There is currently no research on the correlation between novel inflammatory indexes systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and the risk of anemia in chronic kidney disease (CKD) population, as well as survival analysis in CKD with anemia.Methods This investigation encompassed 4444 adult subjects out of the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2018. The study utilized multi-variable logistic regression to assess the relationship between SII, NLR, PLR, and anemia risk occurrence in CKD population. Survival differences in CKD patients with anemia, based on varying levels of SII, NLR, and PLR were evaluated employing Kaplan–Meier and Cox proportional hazards models.Results The adjusted logistic regression model demonstrates that SII, NLR, and PLR are associated with the risk of anemia occurrence in CKD population. Kaplan–Meier’s analysis reveals significant differences in survival rates among CKD patients with anemia stratified by NLR levels. The adjusted Cox proportional hazards model shows that the higher NLR group has a 30% elevated risk of all-cause mortality contrasted with lower group (hazard ratio, HR: 1.30, confidence interval (CI) [1.01, 1.66], p value <.04). Restricted cubic spline (RCS) demonstrates no nonlinear relationship between NLR and all-cause mortality. Lastly, sub-cohort analysis indicates that in populations with diabetes, hypertension, and hyperuricemia, NLR levels have a greater impact on all-cause mortality.Conclusions Controlling inflammation may reduce the occurrence of anemia in CKD populations, with NLR serving to be a potential prognostic indicator for survival results within CKD patients suffering from co-morbid anemia.